1989
DOI: 10.1042/bj2590181
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative and non-oxidative mechanisms in the inactivation of cardiac mitochondrial electron transport chain components by doxorubicin

Abstract: The quinonoid anthracycline, doxorubicin (Adriamycin) is a potent anti-neoplastic agent whose clinical use is limited by severe cardiotoxicity. Mitochondrial damage is a major component of this cardiotoxicity, and rival oxidative and non-oxidative mechanisms for inactivation of the electron transport chain have been proposed. Using bovine heart submitochondrial preparations (SMP) we have now found that both oxidative and non-oxidative mechanisms occur in vitro, depending solely on the concentration of doxorubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 46 publications
2
83
0
1
Order By: Relevance
“…This is not surprising because these sHsps have differences in their amino acid sequences and are localized in different cellular compartments, suggesting an adaptation for precise functions. For example, the overall good chaperone ability of Hsp22 could be an advantage because mitochondria are particularly sensitive to stress (Marcillat et al 1989;Zhang et al 1990;Li et al 2002) and it is possible that mitochondrial proteins are more prone to damage. Moreover, this could explain the beneficial effect that we have obtained by overexpressing this sHsp in the fruit fly (Morrow et al 2004a(Morrow et al , 2004b.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising because these sHsps have differences in their amino acid sequences and are localized in different cellular compartments, suggesting an adaptation for precise functions. For example, the overall good chaperone ability of Hsp22 could be an advantage because mitochondria are particularly sensitive to stress (Marcillat et al 1989;Zhang et al 1990;Li et al 2002) and it is possible that mitochondrial proteins are more prone to damage. Moreover, this could explain the beneficial effect that we have obtained by overexpressing this sHsp in the fruit fly (Morrow et al 2004a(Morrow et al , 2004b.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are the primary source of endogenous superoxide radicals under normal physiological conditions (13), and are susceptible to oxidative damage, especially in myocardial tissue (14,15). Although mitochondrial dysfunction, as documented by inhibition of oxidative phosphorylation, decreased ATP synthesis, and disrupted calcium homeostasis with subsequent cell death, has been observed in ADR-induced cardiac toxicity (1,8,(16)(17)(18)(19), additional subcellular alterations including intracytoplasmic vacuoles, dilated sarcoplasmic reticulum, and myofibril disarray have also been identified (1). Therefore, it is not clear whether mitochondria are indeed the primary target for ADRinduced cardiac toxicity, or whether the mitochondrial injury is a secondary event after the damage of other organelles.…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin acted by redox cycling-independent mechanisms; in contrast, amrubicin acted by a typical redox cycling mechanism, although redox cycling-independent H 2 O 2 formation began occurring as amrubicin concentration was raised from 3 to 10 M. Redox cycling-independent mechanisms of H 2 O 2 formation rest with the formation of complexes between anthracyclines and the mitochondrial phospholipid cardiolipin. These complexes cause functional uncoupling of the mitochondrial electron transport system at the level of complexes I, III, and IV, eventually inducing a passive leakage of reducing equivalents toward molecular oxygen (Marcillat et al, 1989;Simů nek et al, 2009). It is worth noting that cardiolipin deteriorates under ischemic conditions (Sparagna and Lesnefsky, 2009); in the present study, however, myocardial samples had been collected under nonischemic conditions and, hence, we were in a favorable position to unravel processes that depended on doxorubicin-cardiolipin interactions.…”
Section: Discussionmentioning
confidence: 97%
“…Several oxido-reductases were shown to reduce anthracyclines to semiquinone free radicals under defined experimental conditions; these included sarcoplasmic NADPH-cytochrome P450 reductase and cytoplasmic xanthine oxidase (Powis, 1989), the reductase domain of endothelial nitric-oxide synthase (Vá squezVivar et al, 1997), and the multisubunit NADPH oxidase (Deng et al, 2007). On balance, however, more numerous lines of evidence suggest that anthracyclines would be re-duced primarily by the NADH dehydrogenase of complex I of mitochondrial electron transport chain (Davies and Doroshow, 1986;Marcillat et al, 1989;Gille and Nohl, 1997;Wallace, 2003). Confocal microscopy studies confirmed that in isolated cardiomyocytes, mitochondria were the primary site of anthracycline-induced ROS formation (Salvatorelli et al, 2006).…”
Section: Introductionmentioning
confidence: 99%